Endovascular correction of a traumatic internal iliac arteriovenous fistula with a covered stent - Santos Junior,Edson Pedroza dos (2014)
Arteriovenous fistulae (AVFs) are anomalous communications between an artery and a vein, bypassing the capillary network. They can be subdivided on the basis of etiology into congenital and acquired fistulae. The latter may be caused by closed or penetrating traumas, or may be iatrogenic injuries. We report on a case of a young adult female gunshot wound victim treated with emergency laparotomy who developed asymmetrical edema of the lower limbs during the late postoperative period. Imaging exams showed the presence of a left internal iliac AVF, treated using endovascular surgery with placement of a covered stent, resulting in total occlusion of arteriovenous communication.